2022
DOI: 10.1186/s40035-022-00297-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human brain tissue derived from DBS surgery

Abstract: Background Transcriptomic and proteomic profiling of human brain tissue is hindered by the availability of fresh samples from living patients. Postmortem samples usually represent the advanced disease stage of the patient. Furthermore, the postmortem interval can affect the transcriptomic and proteomic profiles. Therefore, fresh brain tissue samples from living patients represent a valuable resource of metabolically intact tissue. Implantation of deep brain stimulation (DBS) electrodes into the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…RNA-sequencing data deposited in the Gene Expression Omnibus (GSE120064) was used to study MC1R expression in human liver biopsy samples from patients diagnosed with NAFLD (n=51) or NASH (n=155) and healthy obese control cases (n=10) without any biochemical or histological evidence or NAFLD ( Govaere et al, 2020 ). Raw data were processed using FIMM-RNAseq data analysis workflow (version 2.0.7) ( Kangas et al, 2022 ). Raw reads were preprocessed using Trim Galore (version 0.6.6).…”
Section: Methodsmentioning
confidence: 99%
“…RNA-sequencing data deposited in the Gene Expression Omnibus (GSE120064) was used to study MC1R expression in human liver biopsy samples from patients diagnosed with NAFLD (n=51) or NASH (n=155) and healthy obese control cases (n=10) without any biochemical or histological evidence or NAFLD ( Govaere et al, 2020 ). Raw data were processed using FIMM-RNAseq data analysis workflow (version 2.0.7) ( Kangas et al, 2022 ). Raw reads were preprocessed using Trim Galore (version 0.6.6).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies also reported proteomic findings for cell or animal models of dystonia associated with the HPRT1 gene 28–31 . One study reported proteomics results for 3 cases with inherited dystonia from material sticking to electrodes used for mapping during deep brain stimulation surgery 32 . Each of these studies revealed some abnormalities likely to be specific to the monogenic disorder studied or the type of sample used, so they are difficult to compare to results reported from the current study.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, an SEEG-based approach has the potential to be applied to other conditions (with confirmed or suspected mosaic mutations) that are treated using deep brain stimulation through intracranial recording electrodes, most notably psychiatric (treatment-resistant depression and obsessive-compulsive disorder, Tourette’s syndrome) or neurologic diseases (Parkinson’s disease, genetic dystonia and tremor). 35 …”
Section: Discussionmentioning
confidence: 99%